1996
DOI: 10.1093/ajcn/64.2.190
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E and vitamin C supplement use and risk of all-cause and coronary heart disease mortality in older persons: the Established Populations for Epidemiologic Studies of the Elderly

Abstract: We examined vitamin E and vitamin C supplement use in relation to mortality risk and whether vitamin C enhanced the effects of vitamin E in 11,178 persons aged 67-105 y who participated in the Established Populations for Epidemiologic Studies of the Elderly in 1984-1993. Participants were asked to report all nonprescription drugs currently used, including vitamin supplements. Persons were defined as users of these supplements if they reported individual vitamin E and/or vitamin C use, not part of a multivitami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
153
2
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(168 citation statements)
references
References 40 publications
9
153
2
4
Order By: Relevance
“…18 Use of vitamin E supplementation reduces the risk of mortality (due to any cause) by 34% and risk of heart disease mortality by 47-63% and cancer risk by 59% as compared to those who are not using vitamin E supplements. 19 Vitamin E supplementation has shown favorable influence on different prostaglandins made by the body. Prostaglandins effects inflammatory response and immune system and also prevent heart disease and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…18 Use of vitamin E supplementation reduces the risk of mortality (due to any cause) by 34% and risk of heart disease mortality by 47-63% and cancer risk by 59% as compared to those who are not using vitamin E supplements. 19 Vitamin E supplementation has shown favorable influence on different prostaglandins made by the body. Prostaglandins effects inflammatory response and immune system and also prevent heart disease and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some other epidemiologic prospective studies found the converse, including the Multiple Risk Factor Intervention Trial, the Elderly Cohort Studies [154], the Rotterdam Study [155], the European Community Multicenter Study on Antioxidants, and the Gruppo Italiano per lo Studio della Sopravvivenza nell Infarto Miocardico prevention trial [156]. The lack of observed association in these studies may be attributable to uncontrolled confounding from unknown or unmeasured confounders such as exercise, diet, concurrent vitamin C depletion or deficiency, and background CVD risk of different study populations.…”
Section: Vitamin E Deficiency and Cvdmentioning
confidence: 96%
“…Similarly, the cardio-protective effect of vitamin E is enhanced and sustained when co-administered with vitamin C [154] due to the synergistic antioxidant effect of both vitamins. The antioxidant activity of alpha-tocopherol results in the production of toxic tocopherol radicals, which are reconverted into alpha-tocopherol by vitamin C and are then reutilized ( Figure 6).…”
Section: Micronutrient Combination/interaction and Effect On Cvdmentioning
confidence: 99%
“…In a Finnish study [40] dietary vitamin E consumption was linked to a reduction in CVD mortality. The Established Populations for Epidemiologic Studies of the Elderly reported a decrease in mortality in particular due to coronary artery disease in elderly people taking vitamin E supplements [51]. As an exception, the Rotterdam study [38] did not reveal a beneficial effect of vitamin E on myocardial infarction.…”
Section: Observational Studies In Apparently Healthy Personsmentioning
confidence: 98%